Investments in sugarcane industry: analysis profile of contractors financing transactions automatic system BNDES the period 2000 2015 - Oliveira, Edenis Cesar (Revista de Administração da UFSM, 2017)
The idiosyncrasies of the sugar-energy sector have been debated and studied exhaustively both in academia and in technical meetings, indicating challenges and opportunities that translate into a perspective of difficult visualization. Therefore, the present study aims to analyze the profile of the automatic financing operations contracted by the National Economic and Social Development Bank (BNDES) system from 2000 to 2015. Characterized as an exploratory study with a quantitative approach, the data were received directly from the BNDES via the Information Access Law (LAI). A total of 60.408 automatic operations were analyzed, with investments totaling R 24.714.610.364. The year 2010 had the highest investment value, representing 13,93% of the total volume of investments in the period, with 6.086 operations. The year 2009 had the highest number of operations in the period – 8.249. In addition, although the median grace period was ten years, the grace period of twelve years recorded 25.996 operations, standing out from the others. The Bank’s largest disbursements were to the “Sugar Production” activity sector, followed closely by investments in “CTV Sugarcane”. There are still new expectations for the Brazilian sugar and ethanol industry.